(untitled) (Journal of Medicine, 2021)
There are a number of gastrointestinal symptoms and complications of COVID-19. Asymptomatic increase in pancreatic enzymes and rarely symptomatic pancreatitis are observed in this disease. This article describes a 37-year-old male suffering from mildly symptomatic COVID-19 infection, who received tablet favipiravir for his management. His condition was improving, when he developed acute pancreatitis, diagnosed clinically, biochemically and also with help of abdominal ultrasound. When he developed this, all typical symptoms of COVID-19 were improved. As a result, role of favipiravir in the development of this pancreatitis was suspected. J MEDICINE JAN 2021; 22 (1) : 69-71